MOTIVASI INDONESIA MENGEKSPOR RUMPUT LAUT KE TIONGKOK TAHUN 2013-2017 - Al Khumaidi Putra; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Seaweed is one of the large potential aquaculture in Indonesia. Indonesia have known one of the largest seaweed producer and exporter in the world. China is the biggest seaweed importer from Indonesia. This study aims to explain the Indonesia’s motivation exporting seaweed to china during 2013-2017.            The research method used in this research is descriptive-qualitative which used secondary data such as books, journals, reports, and the other sources. The perspecrive in this research used liberalism with the level of analysis is the nation state and the international and export theory was used.            The results of this study explain the reasons of Indonesia exporting seaweed to china due to several factors, internal and external factors. The internal factors include indonesia’s high seaweed production which not supported by domestic industry absorption. The external factors include the high demand of china for seaweed and the lack of raw materials for certain types of seaweed.            Keywords: Motivation, Export, Seaweed, Liberalism, International Cooperation